Keunikan Bali dalam Pariwisata Yoga - I Gede Sutarya (UHN IGB Sugriwa Denpasar, 2019)
Yoga tourism is developing in Bali, besides in the place of birth of yoga in India. The search for foreign tourists from yoga to Bali began in the 1970s by bringing yoga teachers themselves. In the 1980s, local yoga teachers began to be absorbed into yoga teachers for foreign tourists. The search for foreign tourists for yoga to Bali raises problems with research on the potential, uniqueness and development of yoga products. This research question is discussed with motivation theory, product theory planning and satisfaction theory. Data was collected by in-depth interviews and questionnaires. The data collected is analyzed qualitatively. The results of the study show that Bali has a yoga potential that develops in its unique culture and ethnicity based on Bali. The highest satisfaction of foreign tourists towards yoga products in Bali lies in culture and ethnicity. Therefore, the development of yoga products in Bali must be based on Balinese culture and ethnicity so that it can become a tourist attraction to Bali. The attraction in the form of cultural and ethnic uniqueness is a differentiator compared to yoga tourism in Bali, with yoga tourism in other places in the world